INTERSEKSI ANTARA PERKAWINAN BEDA AGAMA, SELIBAT, DAN CHILDFREE : PERSPEKTIF USHUL FIQH IMAM AR-RAZI - Khoirul Muhtadin (MAQASHID, 2025)
This research aims to analyze the laws surrounding interfaith marriage and its position amidst the growing trends of celibacy and being childfree in modern society. In the context of increasing religious pluralism, the phenomena of interfaith marriage, celibacy, and being childfree have become complex issues that require in-depth study. The research method employed is qualitative, utilizing a literature review approach, where the data sources include the Qur'an, Hadith, and social facts found in articles, journals, and news reports. Data collection was conducted through documentation studies, while analysis was based on the thoughts of Imam Ar-Razi in his work Al-Mahshul, which provides a Usul Fiqh perspective on these issues. This research is expected to offer a better understanding of the legal status of interfaith marriage, as well as the social and religious implications of the choices of celibacy and being childfree. The results indicate that the laws regarding interfaith marriage can be divided into two categories: permissible and forbidden. Meanwhile, the laws concerning celibacy and being childfree also depend on the intentions and circumstances of the individuals involved, which can either be permissible or forbidden.